Penerapan MYOB Accounting V16 Dalam Pengolahan Data Keuangan PT. Akses Guru Indonesia Depok - Wina Widiati; Jessica Novita Sari Napitupulu (LPPM Universitas Bina Sarana Informatika, 2021)
The needs of computer in this era is crucial in order to gain the effectivity and efficiency of company’s activity. Due to the improvement of information technology, many industries are expected to produce their product with the assistance of computerized system. In this case, accounting has an important role in a company as a factor of company’s decision making in the future. PT. Akses Guru Indonesia Kota Depok is an institution of education. They still use a conventional data processing system which can cause an error and waste of time while processing data. That is the reason behind the making of this scientific writing which titled PT Akses Guru Indonesia Kota Depok’s Financial Data Processing by using MYOB Accounting V.16. The using of this application will help the institution to solve problems and create an effective, efficient, and accurate workflow in order to support all the activities of PT Akses Guru Indonesia Kota Depok.